616 Endocardial lead placement guided by high resolution voltage mapping in a patient with recurrent failure of transvenous pacing system. (8th December 2021) - Vitillo, Paolo; Esposito, Francesca; Rotondi, Francesco; Nappi, Felice; Urraro, Francesco; Laurino, Angela; Russo, Anna; Colimodio, Filomena; Di Lorenzo, Emilio
Abstract: Methods and results: A 58 years-old man was admitted to our intensive care unit for syncope due to inconstant capture of epicardial ventricular lead. His cardiovascular history began 20 years before when he underwent single chamber pacemaker implantation with insertion of a passive fixation ventricular lead for symptomatic complete atrio ventricular block (AVB). Electrical parameters were good at implantation. However, during follow-up a gradual and progressive increase of pacing threshold occurred, with no changes in impedance values, finally leading to complete loss of ventricular capture. Hence, 2 years later, the lead was extracted and a new transvenous ventricular lead was placed in septal position. All electrical parameters were optimal at the end of the procedure. However, in the following months threshold values gradually increased as previously observed. The referring clinicians decided to surgically extract both the device and transvenous lead and to implant an epicardial ventricular lead connected to an abdominal generator. The pacemaker worked properly for about 17 years until he was transferred to our institution with evidence of inconstant lead capture at maximum pacing outputs. A temporary transvenous pacemaker was immediately inserted. Clinical examination, laboratory exams, and echocardiography were normal. Cardiac magnetic resonance (MRI) was not feasible due to the epicardial lead. Thus, in order to obtain cardiac substrate characterization, we decided to perform high density multielectrode voltage mapping of the right ventricular endocardium with HD Grid multielectrode mapping catheter (HD Grid mapping catheter sensor enabled, Abbott Technologies, Minneapolis, MN). Electroanatomic voltage map allows distinction of areas of healthy myocardium (>1.5 mV) from scar tissue (<0.5 mV). Unexpectedly, voltage mapping highlighted no scar zones, showing a globally normal endomyocardial surface. Therefore, a new endocavitary pacemaker was inserted in right prepectoral region and an active fixation right ventricular lead was placed on mid-ventricular septum. A backup pacing lead was placed in a more apical position in an area of endocardial healthy myocardium. Post-procedural sensing, impedance and capture threshold were optimal (0.3 V × 0.4 ms for mid-septal lead and 0.3 × 0.4 ms for the other one). At 1 month follow-up mid-septal lead's threshold was slightly increased (1.0 V × 0.4 ms) and further increase was observed at 3-month outpatient visit (1.75 V × 0.4 ms). Capture threshold of the other lead and other parameters were stable. The patient received remote monitoring for home surveillance of the implanted system. Home monitoring shows a trend toward a progressive increase of pacing threshold of the mid-septal lead and stable value of the other electrode. Conclusions: The present report suggests an innovative use of high-density mapping with HD Grid catheter to characterize endocardial right ventricular myocardium in a patient with contraindication to cardiac MRI and recurrent failure of previous implanted pacing systems for unknown reason and to guide effective lead placement in areas of normal endocardial voltage. Combined use of telemedicine and high-resolution mapping technique allowed us to avoid unnecessary high risk reintervention for novel epicardial lead placement.